Implementasi Node Bridge Untuk Meningkatkan Komunikasi Multi-Node Modul NRF24L01 Pada NLOS - Purwanto, Abdi; Ratiandi Yacoub, Redi; Tjahjamooniarsih, Neilcy (Universitas Harapan Medan, 2024)
Multi-node communication is an important aspect in wireless system development, especially in the context of non-line of sight communications. In this study, we explore the implementation of multi-node communication with bridge nodes to increase distance and reduce packet loss in the NRF24L01 transceiver module. The aim of writing this manuscript is to evaluate the effectiveness of using bridge nodes in improving the quality of multi-node communications on the NRF24L01 module in non-line of sight conditions. This study was carried out through a series of multi-node communication tests with certain configurations, including maximum power usage, 250kbps bit rate, and 5dBi antenna. Tests were carried out at different distances with and without the use of bridge nodes to compare communication performance. Our findings show that a configuration with three client nodes and an NRF24L01 module equipped with a 5dBi antenna is capable of achieving the longest distance of up to 125 m. In non-line of sight conditions, the packet loss rate at a distance of 25-75 m has very good communication quality, with packet loss values ranging from 0-6%. However, at a distance of 100 m, the packet loss percentage exceeds the threshold (15%). The use of bridge nodes succeeded in significantly reducing the packet loss rate, reducing the percentage of packet loss at client nodes C1, C2, and C3 to 6.00%, 6.67%, and 6.33% respectively. Thus, implementing the bridge node has proven effective in improving the quality of communication on the NRF24L01 module in non-line of sight conditions.